Unfair Terms in Standard Digital Contracts: A Hidden Threat to Human Rights and Consumer Justice - Admiral Admiral; Ridwan Arifin; Fadhel Arjuna Adinda; Souad Ahmed Ezzerouali (Yustisia, 2025)
The rise of standard-form digital contracts, such as clickwrap and browsewrap agreements, has changed the way contracts work in the contemporary world by putting efficiency ahead of justice. These contracts make it easier to scale up and access. However, they often include provisions that are not changeable and are unjust, which makes meaningful consent, consumer autonomy, and legal justice less likely. This study examines to explore the legal, ethical, and human rights dimensions of standard form digital contracts. This study uses legal research with comparative analysis of regulatory frameworks and judicial practices in the European Union, the United States, and Indonesia. The study identifies recurrent unfair clauses, including unilateral limitation of liability, forced arbitration, unilateral modification of terms, and excessive personal data exploitation. The findings reveal that formal consent mechanisms in digital contracts often function as legal fictions that obscure structural power imbalances and enable systematic violations of consumer rights and fundamental human rights, particularly the rights to privacy, information, and effective legal remedy. This article also contributes to the development of contemporary contract law by advancing a rights-based and substantive fairness approach to digital contracting, emphasising human dignity, autonomy, and equitable power relations as core standards for assessing contractual validity in the digital economy